Disproportionate use of polysubstance combinations varies by sexual identity among US adults - Luis M. Mestre; Marney A. White; Juhan Lee; Maria A. Parker; Krysten W. Bold (PLoS ONE, 2026)
Polysubstance use is a major public health concern affecting lesbian, gay, and bisexual (LGB) adults, especially bisexual female adults. This study aims to identify the commonly used polysubstance combinations by LGB adults in the past 30 days and to determine whether these combinations differ by sexual identity and sex. Our analytic sample consisted of NSDUH 2021 and 2022 (n = 66,634 adults; 8.59% LGB adults). We used survey-weighted multinomial logistic regression models to assess the polysubstance combinations by sex. The most used substances were binge alcohol drinking, cannabis, cigarettes, and nicotine vape. Bisexual female adults used most of the assessed polysubstance combinations that included binge alcohol drinking, cannabis, or both, often involving three or four substances. Sex differences among the polysubstance combinations vary among heterosexual and bisexual adults but not among gay/lesbian adults. Public health strategies must consider the specific sexual identity, sex, and the types of substance combinations involved.